Toxicity of Ulva lactuca and green fabricated silver nanoparticles against mosquito vectors and their impact on the genomic DNA of the dengue vector Aedes aegypti - Al Thabiani Aziz (IET Nanobiotechnology)
Abstract Marine seaweeds are known to have a potential role against microbial and pesticidal activities. Ulva lactuca, a green macroalgae extract analysed through gas chromatography mass spectrometry reveals 31 compounds. Resistance of mosquito vectors to synthetic insecticides remains a major problem. Discovering and applying natural agents to act against disease vectors is challenging. The activities of the extract and nano‐fabricated green synthesised silver nanoparticles were checked for use against Aedes aegypti and Culex pipiens. The crude extract and synthesised silver nanoparticles exhibited a notable larvicidal effect, and very effective inhibition of pupal and adult emergence. Inhibition of adult emergence of Ae.aegypti was 97.7% and in Cu.pipiens, it was 93.3%. Our genotypic study of Deoxyribonucleic acid from treated larvae utilising random primers MA‐09, MA‐12 and MA‐26 revealed damaged nucleotide sequences when compared with the controls. The antimicrobial activity of both the extract and green synthesised nanomaterials showed prominent activity against pathogenic drug resistant bacteria. Our results contribute to further development of eco‐friendly insecticides with lower cost of preparation. This could further contribute to further research helping future generations to be free from these deadly disease‐causing vectors and pathogenic microbes.